Hydropower Development: Before and After 1992 - Shrestha, Ratna Sansar (Hydro Nepal: Journal of Water, Energy and Environment, 2016)
Hydropower Development Policy promulgated in 1992 by Government of Nepal (GoN) heralded domestic and foreign private investment in hydropower projects, which was instrumental in adding 255,647 MW to the system with the investment of US$ 493 million in a period of 23 years. While, public sector succeeded to add only 238.6 MW during the same period; thus adding a total of 489.14 MW to the system by public and private sectors. As cumulative total installed capacity of projects implemented prior to it in eight decades from 1911 through 1991 was only 239.33 MW, it manifests successful implementation of the policy with resultant mobilization of private investment. Only 9th five-year plan period (1997-2002) succeeded to achieve 91% of the target set for the period resulting in mismatch in the growth of demand and supply; consequently load shedding. The reasons behind the failure need an in-depth analysis and critique of the policy and improvement thereof. HYDRO Nepal Journal of Water Energy and Environment Volume- 18, 2016, January Page -16 to 21